Algorithm for diagnosing operational defects of combine harvester units by videoendoscopy (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article reveals the features of the expanded implementation of diagnostic support for combine harvesters, on the one hand, which is stimulated by steadily increasing requirements for reliability, and on the other hand, the safety of operation of combine harvesters. The purpose of the study was to methodologically substantiate the algorithm for diagnosing operational defects of combine harvester units by video endoscopy. To develop the algorithm for diagnosing the object of study, information about the relationship between informative diagnostic features of the object and its structural parameters was used. Similarly, the basis of the developed diagnostic procedure was a scheme of the main stages of diagnosing mechanisms using the video endoscopic diagnostic system based on the applied program "Diagnost VS", developed at the National University of Life and Environmental Sciences of Ukraine.
Keywords: combine; videoendoscopy; defect; diagnosis